Clinical practice enhanced by interdisciplinary theoretical perspectives - Kirsti Malterud; Susanne Reventlow; Ann Dorrit Guassora (Taylor & Francis Group, 2024)
Background Experience-based knowing in general practice includes advanced interpretation of subjective, complex and particular phenomena in a social context. Enabling different metapositions for reflexivity may provide the accountability needed for such knowing to be recognized as evidence-based practice.Objective To demonstrate and discuss the potential of substantive theories to enhance interpretation of complex challenges in clinical knowing in general practice.Methods We present a fictional case to demonstrate how interdisciplinary substantive theories, with a relevant and specific match to concrete questions, can situate the clinical interaction at an accountable platform. A female patient with Parkinson's disease consults her GP complaining that the disease is restraining her life and threatening her future. The GP has some new ideas from Bandura's theory of self-efficacy and introduces the patient to strategies for further action.Findings The case presents an example of how a relevant substantive theory may offer the GP: 1) a sharper focus for achievement: recognising the issues of fear and identity in chronic, progressive illness, 2) a subsequent position for individualized understanding of adequate strategies: encouraging physical and social activity in a well-known context, and 3) an invitation to consider further possibilities: finding ways to alleviate the burden of fear and progressive decline; engaging in joyful living.Implications General practice knowledge embraces a diversity of sources with different evidence power. The transparency mediated to clinical practice when supported by relevant substantive theories may contribute to recognition of experience-based knowing as evidence-based practice.